TINJAUAN PERKAWINAN KEDUA TANPA PERCERAIAN (POLIANDRI) DALAM ADAT BATAK TOBA DI DESA LUBUK OGUNG KECAMATAN SEI KIJANG KABUPATEN PELALAWAN - Ivan Ryian Ewaldo; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Marriage is an inner and outer bond between a man and a woman as a husband and wife with the aim of forming a happy and eternal family or household based on the Almighty God. Polyandri marriage is a marriage where a wife has two husbands. This is prohibited in religious law and customary law, specifically the Toba Batak adat, but this polyandry marriage has taken place in Lubuk Ogong Village, Seikijang District, Pelalawan Regency. The purpose of this study was to determine the implementation of marriage and divorce in the legitimate Batak Toba customs and to find out the consequences of Christian religious and Batak Toba customs. This type of research can be classified as sociological, because in this study the author immediately conducted research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Lubuk Ogong Village, Seikijang Subdistrict, Pelalawan Regency, while the population and samples were all parties related to the problems examined in this study, data sources used primary data, secondary data, and tertiary data, data collection techniques in research this is by interview and literature study. From the results of the study, two things can be concluded. First, the implementation of polyandry marriage without divorce in the traditional Toba Batak in Lubuk Ogong Village, Sei Kijang Subdistrict, Pelalawan Regency is illegitimate or can not be held the second marriage (polyandry) without any divorce first. Secondly, there is a Batak Toba adat sanction in the form of payment of compensation to the injured party twice as much and payment a divorce mark to the adat leader. First suggestions, the traditional institutions and traditional organizations provide learning and socialization about traditional marriages so that the next generation obeys and preserves. Second, indigenous peoples and traditional institutions uphold the customary law of the Toba Batak people because custom and culture are the identity of the Batak tribe Keywords: Polyandry-Divorce-Batak Toba’s Custom